Coral Tissue Regeneration and Growth Is Associated with the Presence of Stem-like Cells - Jonathan Levanoni; Amalia Rosner; Ziva Lapidot; Guy Paz; Baruch Rinkevich (Journal of Marine Science and Engineering, 2024)
Members of the Cnidaria phylum were studied for centuries to depict the source of their unprecedented regeneration capacity. Although adult stem cells (ASCs) have been recognized in tissue growth/regeneration in many hydrozoans, there has not been any evidence of them in the ancestral Anthozoa class. This study sheds light on the development of epidermal epithelium expansion, akin to blastema, during tissue regeneration after small circular incisions (each 2.77 mm2) and during the natural expansion of tissue across a flat surface in the scleractinian coral Stylophora pistillata. Regeneration was completed within 9 days in 84.5% (n = 64) of the assays. About 35% of the samples regrew a single polyp, 60% showed no polyp regrowth, and approximately 6% exhibited multiple new polyps. We further used histological staining, pH3, Piwi immuno-histochemistry, and qPCR for eight stemness markers: Piwi-1, Nanos-1, Nanos-1-like, Tudor-5, Tudor-7, Boule, Sox-2, and Myc-1. The results revealed the formation of an “addendum”, an epidermal epithelium in the growing edges (in regenerating and normal-growing fronts) inhabited by a cluster of small cells featuring dense nuclei, resembling ASCs, many expressing pH3 as well as Piwi proteins. Most of the stemness genes tested were upregulated. These results indicate the participation of ASCs-like cells in tissue regeneration and growth in scleractinian corals.